Implementasi Bauran Pemasaran Pada Samitech By Samijaya Kabupaten Ponorogo - Defi Ayu Ratnasari (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This research aims to identify and describe the implementation of the marketing mix at Samitech by Samijaya in Ponorogo Regency. This study employs a descriptive research with a qualitative approach. The findings indicate that Samitech by Samijaya has comprehensively implemented the 7P marketing mix strategy. Product, Samitech offers superior products with over 20 categories and 38 reputable brands. Product authenticity is guaranteed through official partnerships and a stringent three-stage quality control, complemented by excellent service. Price, the company adopts competitive and varied pricing. Product pricing is determined by a specialized company team through market research. Place, Samitech utilizes a strategic physical location and implements digital distribution through marketplaces. Promotion, the company leverages social media, marketplace, sales promotions, and advertising. People, organizational structure with well-defined responsibilities. Recruitment is based on specific criteria, and employees provide informative and solution. The company also maintains a uniform identity and dedicated Customer Service. Process, structured purchasing flow, offers diverse payment methods, implements "click and collect" innovation, provides fast delivery, and has efficient warranty claim and product return processes. Physical Evidence, showcases complete and modern facilities, display category system, product demonstration areas, purchase documentation, and product delivery using official company fleets.
Reuploud file repositori 7 Apr 2026_Firli_tata
Keywords: Marketing; Marketing Mix; Electronics Retail